Change in the visual threshold with development of rods in ayu Plecoglossus altivelis - Kawamura, Gunzo; Mukai, Yukinori; Ohta, Hiroyuki (Japanese Society of Fisheries Science, 1984)

(untitled)
This study examined the eye development of ayu fish. Visual threshoild improved with fish growth.